2022
DOI: 10.7759/cureus.21439
|View full text |Cite
|
Sign up to set email alerts
|

A Study to Assess the Quality of Reporting of Animal Research Studies Published in PubMed Indexed Journals: A Retrospective, Cross-Sectional Content Analysis

Abstract: Objectives: A complete and concise pre-clinical experimental research gives detailed information about the disease-specific model, prevents duplication, and saves animal life, money, as well as time. It will also allow readers to effectively interpret and evaluate the work and ensure that others can replicate the experiments described. The present study was conducted to assess the adequacy of animal details provided in published experimental animal studies. Methods: All in vivo studies published as full-text a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Therefore, a gold standard publication checklist (GSPC) was recently proposed for animal studies. Such a list should reduce the number of animals used in preclinical studies and lead to more reliable results thus improving the quality of animalbased scientific articles and follow the idea of evidence-based medicine [5]. it is obvious that more precise international guidelines would increase the methodological quality of animal research and reduce experimental variation, thus helping to better translate the observed results into the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a gold standard publication checklist (GSPC) was recently proposed for animal studies. Such a list should reduce the number of animals used in preclinical studies and lead to more reliable results thus improving the quality of animalbased scientific articles and follow the idea of evidence-based medicine [5]. it is obvious that more precise international guidelines would increase the methodological quality of animal research and reduce experimental variation, thus helping to better translate the observed results into the clinic.…”
Section: Introductionmentioning
confidence: 99%